2004
DOI: 10.1002/ijc.20458
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling program in familial breast cancer: Analysis of its effectiveness, cost and cost‐effectiveness ratio

Abstract: Women with a family history of breast cancer are at increased risk for developing this neoplasm. Starting surveillance more frequently at a younger age than the general population and the possibility of undergoing genetic testing are options for their medical management. We analyzed the benefits and costs of our clinical program in familial breast cancer (FBC) and carried out a cost-effectiveness analysis of such procedure. The benefits and costs of performing genetic counseling and a screening program in FBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
(41 reference statements)
1
31
0
Order By: Relevance
“…A Spanish study from 2004 by Balmana et al examined the cost-effectiveness of surveillance for familial breast cancer and found ICERs that resembled ours; however, since their estimated costs are now over ten years old, their ICERs might be underestimated [24]. More recently, the Swedish National Board of Health and Welfare (SNBHW) published cost-effectiveness evaluations of breast and colorectal cancer screening in the general population.…”
Section: Discussionsupporting
confidence: 54%
“…A Spanish study from 2004 by Balmana et al examined the cost-effectiveness of surveillance for familial breast cancer and found ICERs that resembled ours; however, since their estimated costs are now over ten years old, their ICERs might be underestimated [24]. More recently, the Swedish National Board of Health and Welfare (SNBHW) published cost-effectiveness evaluations of breast and colorectal cancer screening in the general population.…”
Section: Discussionsupporting
confidence: 54%
“…After full text review, a further 21 studies were excluded, leaving 8 studies. 20,21,22,23,24,25,26,27,28 An additional relevant study was identified in the updated literature search. 29 Therefore, a total of nine economic evaluations were included in the systematic review, all published in peer-reviewed journals.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used CEA, 21,22,24 four used CUA, 23,25,27,29 and two used both CEA and CUA. 26,28 All the most recent studies, published from 2009 until 2015, included a CUA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can be an intermediary approach that allows patients the time to make decisions affecting long-term lifestyle. Many factors (eg, ethics, cost) should be considered in discussing options for prevention with very high-risk women, and this area of medicine is a rapidly evolving specialty [18][19][20][21].…”
Section: Molecular Markers For Risk Prediction: Hereditary Predisposimentioning
confidence: 99%